Pemanfaatan Radio Frequency Identification dan Near Field Communication pada PKK Pondok Rajeg Residence - Ika Mei Lina; Gilang Ryan Fernandes; Kevin Septianzah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
PKK is an abbreviation for Family Empowerment and Welfare, a national movement in community development that grows from, by and for the community towards the realization of a healthy, prosperous family, environmental awareness, faith and devotion to God Almighty. Based on the results of interviews and observations carried out by the community service team, it is known that various problems exist within the Pondok Rajeg Residence PKK, that so far, Pondok Rajeg Residence PKK members are still experiencing difficulties in carrying out innovations in entrepreneurship. Pondok Rajeg Residence PKK members are still doing it manually to view profiles. and menus for sale. Therefore, the team proposing community service considers it necessary to provide understanding in the introduction and use of Radio Frequency and Near Field Communication in order to make it easier for administrators and members to provide entrepreneurial services to the PKK Pondok Rajeg Residence.